Landasan Konstitusional Keistimewaan Daerah Istimewa Yogyakarta Dalam Perspektif Hukum Tata Negara - Kusuma Dewi, Indah; Hardin; Andara, Darojatun (UNIB Press, 2026)
This study examines the special status of the Special Region of Yogyakarta (DIY) within the framework of the regional government system from a constitutional perspective. Historically, the special status of DIY is rooted in the existence of the Ngayogyakarta Hadiningrat Sultanate and the Pakualaman Duchy, which had their own governance systems before becoming part of the Unitary State of the Republic of Indonesia. This integration was affirmed through the 1945 political mandate that became the basis for the legitimacy of DIY's special status. From a legal perspective, recognition of DIY's special status is stated in the 1945 Constitution of the Republic of Indonesia, specifically Article 18 and Article 18B, which provides space for regions with certain special or special characteristics. Law Number 13 of 2012 stipulates that special authority includes institutional aspects, culture, land, spatial planning, and the mechanism for filling the gubernatorial position. The results of the study indicate that DIY's special status is a form of asymmetric decentralization that has constitutional legitimacy. Although the appointment of regional heads contains elements of monarchy, this does not conflict with the principles of democracy and the rule of law, as it remains within the constitutional framework and the national government system. The Special Region of Yogyakarta (DIY) reflects a blend of historical values, local culture, and a modern legal system within the context of a pluralistic nation. DIY can be viewed as an ideal model for implementing regional governance based on special rights, in line with the principles of the Indonesian constitution.